Pengaruh Kompensasi, Pelatihan Dan Pengembangan Terhadap Kinerja Pegawai Badan Penanggulangan Bencana Daerah Kabupaten Toraja Utara - Musa, Romi; Marampa, Adriana Madya; Biringkanae, Asrtiwati (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The type of research used is a quantitative descriptive approach. The number of samples used in this research was 32 respondents. The data collection procedures for this research were: Observation and Questionnaire. Using multiple linear analysis with SPSS Version 27. The partial results of this research include compensation and development variables that do not have a positive and significant effect on employee performance at the North Toraja Regency Regional Disaster Management Agency. Meanwhile, training has a positive and significant effect on employee performance at the North Toraja Regency Regional Disaster Management Agency. Meanwhile, the results of research simultaneously show that the variables of compensation, training and development simultaneously have a positive and significant effect on employee performance at the North Toraja Regency Regional Disaster Management Agency.